ANALISIS PRODUKSI BERAS TIAP PROVINSI DI INDONESIA TAHUN 2011-2016 - Muhammad Syarifuddin; Ida Nuraini; M. Sri Wahyudi (Program Studi Ekonomi Pembangunan, 2019)
The purpose of this study was to determine the development and distribution of each variable, as well as the effect of the variable Land Area and Productivity on Rice Production in each Province and island in Indonesia for the period 2011-2016. The analytical tool used is panel data regression. From the test results obtained the coefficient of determination R ^ 2 for the fixed effect model of 0.997. This shows that the ability of independent variables in explaining the dependent variable is 99.7%. The results of the study concluded that simultaneous planting of land area, and productivity had a positive and significant effect on rice production, with the results of the statistical F test of 1960,397 greater than the F table of 3,30. While the partial test results show that land area and productivity have a positive and significant effect on rice production in Indonesia.